Acute coronary syndromes in young patients: Phenotypes, causes and clinical outcomes following percutaneous coronary interventions. (1st March 2022) - Zanchin, Christian; Ledwoch, Stefan; Bär, Sarah; Ueki, Yasushi; Otsuka, Tatsuhiko; Häner, Jonas D.; Zanchin, Thomas; Praz, Fabien; Hunziker, Lukas; Stortecky, Stefan; Pilgrim, Thomas; Losdat, Sylvain; et al.
Abstract: Background: The prevalence of acute coronary syndromes (ACS) among young individuals is increasing, but the phenotypic characteristics, causes and clinical outcomes in this group have not been well described. Methods: Between 2009 and 2017, 8712 ACS patients underwent percutaneous coronary intervention (PCI) and were prospectively enrolled. We defined a young patient as female <50 years and male <45 years. The causes of ACS were defined by an adjudication committee. The primary endpoint was the patient-oriented composite endpoint (POCE) of all-cause mortality, myocardial infarction or any revascularization at 12 months. Results: Among 8712 ACS patients, 472 (5.4%) patients were young (26% female). The main cause of ACS in young patients was atherosclerosis (86.5%), followed by coronary artery embolism (9%), and spontaneous coronary artery dissection (SCAD) (4.5%). POCE occurred less frequently in young compared to old patients (8.5% vs. 16.7%, hazard ratio 0.48 (95% confidence interval 0.35–0.66), p  < 0.001). The rates of the individual components of the POCE were lower in young including all-cause mortality (3.2% versus 9.5%, 0.32 (0.19–0.54), p  < 0.001), myocardial infarction (1.9% versus 3.7%, 0.49 (0.25–0.95), p  = 0.035) and any revascularization (5.1% versus 7.4%, 0.65 (0.43–0.97), p  = 0.037). Young patients with SCAD had a higher rate of death as compared to those with atherosclerosis, mainly attributed to cardiac deaths. Conclusions: One out of 20 ACS patients undergoing PCI was young and the principal cause was atherosclerosis. Young carry a lower risk for future events compared to older ACS patients. The underlying cause leading to ACS should be considered in appropriate risk stratification of young patients. Clinical Trial Registration: Clinicaltrials.gov . NCT02241291 Highlights: Approximately one out of 20 ACS patients undergoing PCI for ACS was young (female <50 years, male <45 years). The principal mechanism of ACS in young patients was atherosclerosis (86.5%), followed by coronary artery embolism (CAE) (9%), and spontaneous coronary artery dissection (SCAD) (4.5%). As compared to older patients, young patients had a lower risk for the primary endpoint POCE and for its individual components at 12 months.